Musculoskeletal Disorder among Municipal Solid Waste Collectors - Ezrin Hani, Sukadarin; Junaidah, Zakaria (Environmental and Occupational Health Society, 2017)

(untitled)
Objective: This cross sectional study investigates the prevalence of MSDs among solid waste collectors.Method: Data collection was conducted through face to face structured interviews with waste collectors using Nordic. Musculoskeletal Questionnaire (NMQ). Next, Rapid Upper Limb Assessment (RULA) was used to observe the workers’ exposure to the risk factors. Result: Results revealed that, the highest prevalence of MSDs symptoms during last 12 months is low back pain (54.50%) followed by upper back pain (27.30%) and at shoulder region (22.70%). RULA analysis of the observed results showed that 43.20% of the waste collectors have scored 7 indicates postural changes must be done immediately. Meanwhile 45.5% of waste collectors scored 5 an indication of postural changes must be carried out soon. From the chi-square analysis, the results displayed a significant association between neck and low back pain prevalence with the identified risk level at p<0.05. Conclusion: Findings from this study provided an evidence of a significant association between MSDs symptoms reported in NMQ and the risk level exposed by the respondents obtained by RULA. Physical demanding activities among waste collectors such as handling heavy workload, awkward posture and repetitive task might be the reason of the association.